2021
DOI: 10.3390/jcm10051097
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Microbiome Characteristics in Female Patients with Acute Uncomplicated Cystitis and Recurrent Cystitis

Abstract: Traditionally, the diagnostic mainstay of recurrent urinary tract infection has been urinary culture. However, the causative uropathogen of recurrent cystitis has not been well established. Urine DNA next-generation sequencing (NGS) can provide additional information on these infections. Herein, we compared urine NGS results and urine cultures in patients with acute uncomplicated cystitis (AUC) and recurrent cystitis (RC), and evaluated the difference in microbiome patterns in the NGS results. Patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 46 publications
(51 reference statements)
1
38
0
Order By: Relevance
“…Pseudomonas, Acinetobacter, and Enterobacteriaceae were identified in the urine NGS findings for the AUC group, while Sphingomonas, Staphylococcus, Streptococcus, and Rothia spp. were detected in the RC group [46]. Significant variations in bacterial diversity and patterning were seen between AUC and RC patients.…”
Section: Uti and Urinary Microbiomementioning
confidence: 85%
See 2 more Smart Citations
“…Pseudomonas, Acinetobacter, and Enterobacteriaceae were identified in the urine NGS findings for the AUC group, while Sphingomonas, Staphylococcus, Streptococcus, and Rothia spp. were detected in the RC group [46]. Significant variations in bacterial diversity and patterning were seen between AUC and RC patients.…”
Section: Uti and Urinary Microbiomementioning
confidence: 85%
“…Significant variations in bacterial diversity and patterning were seen between AUC and RC patients. This study suggests that AUC can be considered a transient infection produced by a single pathogenic organism, while dysbiosis seems to play a more significant role in the pathophysiology of RC [46,47]. RC may be linked with urinary tract dysbiosis, but more study is necessary [46,48].…”
Section: Uti and Urinary Microbiomementioning
confidence: 89%
See 1 more Smart Citation
“…CD is associated with damage to the glycosaminoglycan (GAG) layer, which appears to exhibit histopathological characteristics similar to those of IC. This suggests a new possibility that the immune inflammatory reaction is caused by dysbiosis of the microbiota in the bladder rather than simply causing IC/BPS due to infection by specific bacteria [7,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…12 Through a previous pilot study, we demonstrated the difference in bacterial diversity and patterns between RC and acute uncomplicated cystitis. 13 Due to these new techniques, a new disease pathway through gut-vagina-bladder crosstalk has gained focus apart from the traditional mechanism of UTI, which was mainly caused by gut-bladder crosstalk. 7,8,14,15 Such changes in study perspectives can provide good therapeutic clues, particularly in RC, which is di cult to treat with frequent recurrence.…”
Section: Introductionmentioning
confidence: 99%